Relationship between money supply and government revenues in Nigeria - Yakubu Musa; Umar Usman; Aminu Bello Zoramawa (CBN Journal of Applied Statistics, 2014)
The insights on the long run relationship amongst money supply and government revenues are of significant importance for monetary-fiscal policy formulation in a developing country like Nigeria. Taking into account the vital importance of these two variables, we empirically analyzed the long-run relationships and dynamic interactions between the money supply (broad money M2) and government revenues in Nigeria using an Autoregressive Distributed Lag (ARDL) bounds testing approach. The study spans the period 1970 to 2010. From the results, it is evident that there is the existence of a long run relationship between money supply and revenues when money supply is made the dependent variable. When revenue was made the dependent variable, no evidence of a long run relationship was found. This indicates that changes in government revenues in the past have significantly affected the money supply as macroeconomic indicator in the country economy. The estimated coefficient of revenues has a positive and significant impact on money supply. A 1% increase in revenues leads to approximately 0.96% increase in the Money supply at long run. The sign of the short-run dynamic impacts of these variables are significant and have the correct sign. The error correction mechanism (ECM) is estimated as - 0.17 and -0.28%, this means that government revenue and money supply have significant short term effect.
Keywords: E51; E63; H2; 330; Money supply; Government revenues; ARDL; Cointegration